Pemberdayaan Sumber Daya Lokal Dalam Pembuatan Aquaponik Di Pantai Cemara Balikpapan - Andhika Giyantara; Daffa Akmalludin Arrizal; Muhammad Syaiful Umara; Meyrina Faradhea Puspitasari; Ario Trapsilo Wibowo; Ade Zhalsa Bila; Reza Laurina; Sebrine Adilia Putri (AMMA : Jurnal Pengabdian Masyarakat, 2024)
An environmentally friendly technological system that can be utilized as a food source is the aquaponic system. Aquaponics is a way of farming that combines aquaculture and hydroponics, the goal is to raise fish and plants in a circulated environment and interconnected system. The advantage of the aquaponic system is that fish waste can be used as a source of organic fertilizer that is good for plant growth and the products produced are organic products because they only use fertilizer from fish waste that has gone through a biological process. Aquaponics applies a natural ecological system in which there is a mutually beneficial relationship between fish and plants. The application of aquaponics on Cemara beach can improve the economy of the community and as one of the sources of attraction of this tourist spot.